Binary polyethylene composition for lithium battery diaphragm as well as preparation method and application of binary polyethylene composition

The binary polyethylene composition prepared by single-kettle multi-stage polymerization technology solves the contradiction between the processing performance and physical and mechanical properties of lithium battery separators, and realizes high-strength and good processing performance separators, which are suitable for the application of lithium batteries.

CN119409857APending Publication Date: 2025-02-11CHINA CHEM TECH RES INST

Patent Information

Application Number
CN202411331634.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

There is a contradiction between the processing performance and physical and mechanical properties of the existing lithium battery membrane, resulting in insufficient strength of the membrane and difficulty in processing.

Method used

Using single-kettle multi-stage polymerization technology, low molecular weight polyethylene with an intrinsic viscosity of 2 to 5 dl/g and an intrinsic viscosity of 6 to 12 dl/ g. Binary composition of ultra high molecular weight polyethylene.

Benefits of technology

It achieves high strength and good processing performance of lithium battery separators, with low porosity, strong breathability and strong needle puncture performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409857A_ABST
    Figure CN119409857A_ABST
Patent Text Reader

Abstract

The invention provides a binary polyethylene composition for a lithium battery diaphragm as well as a preparation method and application of the binary polyethylene composition. The preparation method comprises the following steps: S1, carrying out first polymerization reaction on ethylene to obtain low molecular weight polyethylene with intrinsic viscosity of 2-5dl / g; the temperature of the first polymerization reaction is 60-80 DEG C, the pressure is 0.4-0.8 mPa, and the mass ratio of ethylene to hydrogen is (6000-4000): 1; s2, ethylene is subjected to a second polymerization reaction, and extra-high molecular weight polyethylene with the intrinsic viscosity of 6-12 dl / g is obtained; the temperature of the second polymerization reaction is 75-90 DEG C, the pressure is 0.5-1 mPa, and the mass ratio of ethylene to hydrogen is 4000-2000: 1; the binary polyethylene composition for the lithium battery diaphragm comprises low-molecular-weight polyethylene and extra-high-molecular-weight polyethylene. The invention effectively solves the problem of difficult processing of extra-high molecular weight polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer chemistry, and in particular to a binary polyethylene composition for lithium battery separators, and a preparation method and application thereof. Background Art

[0002] Ultra-high molecular weight polyethylene powder can be used in many fields such as films, sheets, microporous membranes, fibers, foams, tubes, etc., especially as a raw material for microporous membranes used as separators for secondary batteries represented by lead-acid batteries and lithium-ion batteries. This is because of its high molecular weight, excellent tensile processability, high strength, high chemical stability, and excellent long-term reliability.

[0003] As an important accessory for electric vehicles, electric bicycles, mobile phones, and computers, lithium batteries have a very broad development prospect. In the structure of lithium batteries, the diaphragm is one of the key inner components. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle, and safety performance. The diaphragm with excellent performance plays an important role in improving the comprehensive performance of lithium batteries. At present, the wet process is mainly used to prepare lithium battery diaphragms. Due to processing and production efficiency issues, polyethylene lithium battery diaphragms now use polyethylene with a lower molecular weight, which is generally 400,000 to 1.2 million, that is, ultra-high molecular weight polyethylene.

[0004] In order to reduce costs, thinning the film thickness is a development trend. However, the problem caused by thinning the film is that the film strength is reduced. The way to improve the film strength is to increase the molecular weight of polyethylene. However, the increase in the molecular weight of polyethylene brings about the problem of difficult processing. In order to improve the processing performance, chemical modification or physical modification can be carried out, such as adding various internal and external lubricants and nucleating agents. The entry of these substances during the extrusion process will cause the flow orientation of the polyethylene super-large molecules along the extrusion direction due to the effect of "solvation". As a result, the biaxial stress difference of the pipe in the axial and circumferential directions will be very obvious. This modification method is also used in the field of lithium battery separators. Most lithium battery separator companies now use polyethylene with a characteristic viscosity of 6dl / g, such as Celanese's This type of polyethylene has the characteristics of easy processing, but it also has the disadvantage of insufficient strength. For this reason, some companies use a slightly higher molecular weight Polyethylene with an intrinsic viscosity of 10 dl / g. Although the performance of this polyethylene membrane is improved, its processability is reduced. Then the method to improve this polyethylene is to blend two polyethylenes in different proportions, such as The mass ratio is 7:3 or 6:4. The blending method solves the processability and physical mechanical properties to a certain extent. However, there are still some problems. For example, due to the unevenness of the blending, the produced diaphragm has crystal points and the performance of the diaphragm is unstable. There is also a mixture of commercially available HDPE and ultra-high molecular weight polyethylene. Since they are produced by different manufacturers, the particle size of the polyethylene is different, resulting in uneven dissolution during the dissolution process.

[0005] CN108368185A discloses a method for producing multimodal ultra-high molecular weight polyethylene, which is polymerized in three cascade reactors, and a low molecular weight polyethylene with a weight average molecular weight (Mw) of 20,000 to 90,000 g / mol is produced in the first reactor under high hydrogen conditions, and its slurry is transferred to the second reactor after the dehydrogenation unit to produce a medium molecular weight polyethylene with a weight average molecular weight (Mw) of 150,000 to 1000000 g / mol, and finally the slurry is transferred to the third reactor to produce a molecular weight of 1000000 to 5000000 g / mol ultra-high molecular weight polyethylene. The polymer ratio of the three reactors is 30-55 / 10-25 / 25-40. This method can prepare ultra-high molecular weight polyethylene with good processability and good physical properties. However, it is not suitable for the existing domestic ultra-high molecular weight polyethylene production process.

[0006] CN107880197A discloses a method for preparing bimodal ultra-high molecular weight polyethylene in a single reactor operation. The method adopts segmented polymerization. The optimal conditions for the first segment polymerization are 80°C, pressure 1.8mPa, and reaction time 2 hours; the optimal conditions for the second segment polymerization are 70°C, pressure 1.0mPa, and reaction time 4 hours. The molecular weight of the polyethylene produced in the first segment is 500,000 to 1,000,000 (viscosity average molecular weight), and the molecular weight of the polyethylene produced in the second segment is 1,000,000 to 3,000,000 (viscosity average molecular weight).

[0007] However, the polymerized olefins obtained in the above patents still have defects and cannot be used to prepare products with good processability, nor can they be used to prepare lithium battery separators. This is because the molecular weight of the polymer in the low molecular weight part is not low enough and is far from the molecular weight range of high-density polyethylene.

[0008] Therefore, there is still a need in the prior art to develop a new method for multi-component polymerization, especially for maintaining the strength and further improving the processing performance of ultra-high molecular weight polyethylene. Summary of the invention

[0009] In order to solve the above problems in the prior art, the purpose of the present invention is to provide a binary polyethylene composition for lithium battery separator and its preparation method and application. The present invention effectively solves the problem of difficulty in processing ultra-high molecular weight polyethylene.

[0010] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a binary polyethylene composition for a lithium battery separator is provided, which comprises:

[0011] S1, subjecting ethylene to a first polymerization reaction to obtain a low molecular weight polyethylene having an intrinsic viscosity of 2 to 5 dl / g; the temperature of the first polymerization reaction is 60 to 80° C., the pressure is 0.4 to 0.8 mPa, and the mass ratio of ethylene to hydrogen is 6000 to 4000:1;

[0012] S2, subjecting ethylene to a second polymerization reaction to obtain ultra-high molecular weight polyethylene with an intrinsic viscosity of 6 to 12 dl / g; the temperature of the second polymerization reaction is 75 to 90° C., the pressure is 0.5 to 1 mPa, and the mass ratio of ethylene to hydrogen is 4000 to 2000:1;

[0013] The binary polyethylene composition for lithium battery separator comprises the low molecular weight polyethylene and the ultra high molecular weight polyethylene.

[0014] The preparation method of the present invention belongs to single-pot multi-stage polymerization, which is more in line with the process of preparing ultra-high molecular weight in existing production practice. In addition, according to the method of the present invention, the reaction conditions of the first stage polymerization and the second stage polymerization, especially the hydrogenation amount conditions, are accurately controlled, and suitable low molecular weight polyethylene and ultra-high molecular weight polyethylene are effectively prepared, and the obtained binary composition has good strength and good processability.

[0015] In some preferred embodiments of the present invention, the mass ratio of the low molecular weight polyethylene to the ultra high molecular weight polyethylene is 10 to 50: 50 to 90. The composition composed according to such a preferred ratio has better strength and processability.

[0016] In some preferred embodiments of the present invention, the systems of the first polymerization reaction and the second polymerization reaction include a diluent, a catalyst, and a co-catalyst;

[0017] Preferably, the molar ratio of aluminum in the co-catalyst to titanium in the titanium catalyst is 10-150; preferably 20-100.

[0018] In some preferred embodiments of the present invention, the diluent includes one or a combination of two or more of hexane, isopentane, and heptane; preferably, the diluent includes hexane. The diluent is usually determined according to the volume (capacity) of the reaction vessel (e.g., reactor), generally set to 1 / 2-2 / 3 of the volume (capacity) of the reaction vessel, and the final reaction slurry concentration is 20-35%. The present invention does not further limit the amount of the diluent.

[0019] In some preferred embodiments of the present invention, the catalyst comprises a Ziegler-Natta catalyst. The catalyst selected in the present invention may be a metallocene catalyst or a non-metallocene catalyst. Preferably, the present invention does not make further requirements for the specific selection of the Ziegler-Natta catalyst.

[0020] In some preferred embodiments of the present invention, the co-catalyst includes an alkyl aluminum; preferably, the co-catalyst includes one or a combination of two or more of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trioctylaluminum, diethyl aluminum chloride, diisobutyl aluminum chloride, sesquiethylaluminum chloride, and ethylaluminum dichloride; preferably, the co-catalyst includes triethyl aluminum and / or triisobutyl aluminum.

[0021] In some preferred embodiments of the present invention, the first polymerization reaction and the second polymerization reaction are carried out under a protective atmosphere, preferably comprising nitrogen.

[0022] According to another aspect of the present invention, there is also provided a binary polyethylene composition for lithium battery separator prepared according to the above method.

[0023] In some preferred embodiments of the present invention, the binary polyethylene composition for lithium battery separator satisfies one or a combination of two or more of the following conditions:

[0024] The intrinsic viscosity is 5 to 8 dl / g;

[0025] The melt index tested according to ASTMD 1238 is 0.05-0.6 g / 10 min;

[0026] D50 is 110-130 microns;

[0027] D90-D10 / D50 is 0.6 to 0.8;

[0028] Mw is 450000~700000;

[0029] Mn is 90000~130000.

[0030] According to another aspect of the present invention, there is also provided a lithium battery separator obtained by preparing a film from the above-mentioned binary polyethylene composition for lithium battery separator through a wet molding process, and then biaxially stretching the film. The method for processing and molding the film may be conventional in the art, and the present invention does not further limit it. The lithium battery separator obtained by the present invention has excellent properties, including thin thickness, high tensile strength, low porosity, strong air permeability, and strong needle puncture performance. Therefore, the present invention provides a lithium battery separator with broad application prospects.

[0031] According to another aspect of the present invention, a lithium battery comprising the lithium battery separator is also provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A SEM image of the catalyst used in the present invention is shown. DETAILED DESCRIPTION

[0033] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0034] In the following examples and comparative examples, unless otherwise specified, the catalyst used was prepared by the following method:

[0035] 0.5mol (in terms of Mg) active MgC12 carrier, 200mL decane and 260mL isooctyl alcohol (1.67mol) were heated to 130℃ for 60 minutes, cooled to 65℃, and 0.167mol alkoxysilane (a mixture of γ-chloropropyltriethoxysilane and γ-chloropropyltrimethoxysilane, with a molar ratio of 8:1) and 0.15mol norbornene anhydride were added at this temperature, and the reaction continued for 60 minutes, and then cooled to room temperature. At 0℃, it was slowly added dropwise to 2000mL TIC14 for 90 minutes, with a stirring speed of 1000 rpm. After the addition was completed, the temperature was kept at 0℃ for 60 minutes, and then the temperature was slowly raised to 110℃ for 120 minutes. At this temperature, 0.05mol of the same silane electron donor was added, and the reaction continued for 120 minutes to obtain a solid catalyst. After stopping stirring, it was found that the solid catalyst particles settled very quickly. After the reaction was completed, the solid catalyst was filtered out hot. Wash with hexane, 400 mL each time, until the filtrate is basically colorless, and the free titanium content is less than 0.3 mg / mL. After drying, a solid catalyst is obtained, which is recorded as ZN catalyst. The catalyst is spherical, and the element analysis is: Ti: 4.15%, Mg: 15.5%, Si: 1.02%, and the particle size is 3.0 μm. The SEM image of the catalyst is as follows Figure 1 As shown (Hitachi Regulus8100 test).

[0036] Example 1

[0037] This embodiment provides a method for preparing a binary polyethylene composition for a lithium battery separator, comprising:

[0038] S1, in a 10-liter stainless steel autoclave, after nitrogen replacement, 5 liters of dehydrated hexane, a hexane solution of triethylaluminum (with an Al / Ti molar ratio of 100), and 60 mg of ZN catalyst were added in sequence, the stirring speed was 1000 rpm, the temperature was raised to 60° C., ethylene and hydrogen (ethylene / hydrogen mass ratio 5500:1) were introduced until the autoclave pressure reached 0.6 MPa (gauge pressure), and the first polymerization reaction was carried out at a polymerization temperature of 75° C. while maintaining the autoclave pressure at 0.6 MPa;

[0039] S2, when the ethylene absorption reaches 100g, stop introducing ethylene and hydrogen, raise the temperature to 85°C, then introduce ethylene and hydrogen (ethylene / hydrogen mass ratio 4000:1), and stop the second polymerization reaction when the ethylene absorption reaches 1000g. When the pressure in the kettle drops below 0.2 after suction and pressure, cool to 40°C, discharge the material, and dry the sample to obtain a binary polyethylene composition for lithium battery separators.

[0040] The analysis results are as follows: intrinsic viscosity: 6.17 dl / g, melt index (21.6 kg): 0.45, bulk density: 0.45 g / cm 3 , particle size (D50): 123μm, particle size distribution (D90-D10 / D50): 0.68.

[0041] Example 2

[0042] The difference from Example 1 is that the diluent is 5 liters of dehydrated pentane, and the first stage polymerization reaction is controlled to obtain 200 g of low molecular weight polyethylene. Finally, the temperature is lowered to 25° C. and the material is discharged.

[0043] The analysis results are as follows: intrinsic viscosity: 6.80 dl / g, melt index (21.6 kg): 0.28, bulk density: 0.45 g / cm 3 , particle size (D50): 119μm, particle size distribution (D90-D10 / D50): 0.65.

[0044] Example 3

[0045] The difference from Example 1 is that 6 L of dehydrated heptane is used as the diluent, and the first stage polymerization reaction is controlled so as to obtain 300 g of low molecular weight polyethylene.

[0046] The analysis results are as follows: intrinsic viscosity: 7.21 dl / g, melt index (21.6 kg): 0.19, bulk density: 0.45 g / cm 3 , particle size (D50): 117μm, particle size distribution (D90-D10 / D50): 0.69.

[0047] Example 4

[0048] The difference from Example 1 is that the first stage polymerization reaction is controlled so as to obtain 400 g of low molecular weight polyethylene.

[0049] The analysis results are as follows: intrinsic viscosity: 7.60 dl / g, melt index (21.6 kg): 0.11, bulk density: 0.45 g / cm 3 , particle size (D50): 125μm, particle size distribution (D90-D10 / D50): 0.61.

[0050] Example 5

[0051] The difference from Example 1 is that the first stage polymerization reaction is controlled so as to obtain 500 g of low molecular weight polyethylene.

[0052] The analysis results are as follows: intrinsic viscosity: 8.03 dl / g, melt index (21.6 kg): 0.05, bulk density: 0.45 g / cm 3 , particle size (D50): 124μm, particle size distribution (D90-D10 / D50): 0.69.

[0053] Example 6

[0054] The difference from Example 1 is that the catalyst used is a Ziegler-Natta catalyst with the brand DJD-PES-B produced by Liaoning Dingjide Petrochemical Co., Ltd.

[0055] The analysis results are as follows: intrinsic viscosity: 7.96 dl / g, melt index (21.6 kg): 0.07, bulk density: 0.44 g / cm 3 , particle size (D50): 132μm, particle size distribution (D90-D10 / D50): 0.65.

[0056] Example 7

[0057] The difference from Example 1 is that the catalyst used is Ziegler-Natta catalyst with the brand DJD-PES-B produced by Liaoning Dingjide Petrochemical Co., Ltd., and the mass ratio of ethylene / hydrogen in the second polymerization reaction stage is 2000:1.

[0058] The analysis results are as follows: intrinsic viscosity: 6.63 dl / g, melt index (21.6 kg): 0.24, bulk density: 0.44 g / cm 3 , particle size (D50): 138μm, particle size distribution (D90-D10 / D50): 0.64.

[0059] Example 8

[0060] The difference from Example 1 is that the mass ratio of ethylene to hydrogen in the first polymerization reaction stage is 6000:1.

[0061] The analysis results are as follows: intrinsic viscosity: 6.40 dl / g, melt index (21.6 kg): 0.33, bulk density: 0.45 g / cm 3 , particle size (D50): 120μm, particle size distribution (D90-D10 / D50): 0.66.

[0062] Comparative Example 1

[0063] The difference from Example 1 is that no hydrogen is added in the first polymerization stage.

[0064] The analysis results are as follows: intrinsic viscosity: 7.11 dl / g, melt index (21.6 kg): 0.19, bulk density: 0.45 g / cm 3 , particle size (D50): 125μm, particle size distribution (D90-D10 / D50): 0.68.

[0065] Comparative Example 2

[0066] The difference from Example 1 is that the mass ratio of ethylene to hydrogen in the first polymerization reaction stage and the second polymerization reaction stage is 6000:1.

[0067] The analysis results are as follows: intrinsic viscosity: 8.50 dl / g, melt index: undetectable, bulk density: 0.45 g / cm 3 , particle size (D50): 127μm, particle size distribution (D90-D10 / D50): 0.63.

[0068] Comparative Example 3

[0069] The difference from Example 1 is that the mass ratio of ethylene to hydrogen in the first polymerization reaction stage is 3000:1, and the mass ratio of ethylene to hydrogen in the second polymerization reaction stage is 4000:1.

[0070] The analysis results are as follows: intrinsic viscosity: 5.35 dl / g, melt index (21.6 kg): 0.63, bulk density: 0.45 g / cm 3 , particle size (D50): 129μm, particle size distribution (D90-D10 / D50): 0.61.

[0071] Comparative Example 4

[0072] A polyethylene standard sample, denoted as S1, is prepared as follows:

[0073] In a 10-liter stainless steel autoclave, after nitrogen replacement, 5 liters of dehydrated hexane, hexane solution of triethylaluminum (according to the Al / Ti molar ratio of 100), and 60 mg of high hydrogen sensitivity catalyst were added in sequence, the stirring speed was 1000 rpm, the temperature was raised to 60°C, and ethylene and hydrogen were introduced until the autoclave pressure was 0.6 MPa (gauge pressure) (ethylene / hydrogen mass ratio 5500:1, at a polymerization temperature of 75°C, the autoclave pressure was maintained at 0.6 MPa. After the polymerization reaction was carried out for 2 hours, the polymerization reaction was stopped. When the pressure in the autoclave dropped below 0.2 after suction pressure, the temperature was lowered to 40°C, the material was discharged, and the sample was dried to obtain a polyethylene standard sample S1. The analysis results are as follows: intrinsic viscosity: 9.98 dl / g, melt index: undetectable, bulk density: 0.45 g / cm 3 , particle size (D50): 118μm, particle size distribution (D90-D10 / D50): 0.67.

[0074] Comparative Example 5

[0075] A polyethylene standard sample, denoted as S2, is prepared as follows:

[0076] In a 10-liter stainless steel autoclave, after nitrogen replacement, 5 liters of dehydrated hexane, hexane solution of triethylaluminum (according to the Al / Ti molar ratio of 100), and 60 mg of high hydrogen sensitivity catalyst were added in sequence, the stirring speed was 1000 rpm, the temperature was raised to 60°C, and ethylene and hydrogen were introduced until the autoclave pressure was 0.6 MPa (gauge pressure) (ethylene / hydrogen mass ratio 4000:1, at a polymerization temperature of 85°C, the autoclave pressure was maintained at 0.6 MPa. After the polymerization reaction was carried out for 2 hours, the polymerization reaction was stopped. When the pressure in the autoclave dropped below 0.2 after suction pressure, the temperature was lowered to 40°C, the material was discharged, and the sample was dried to obtain a polyethylene standard sample S2. The analysis results are as follows: intrinsic viscosity: 6.08 dl / g, melt index (21.6 kg): 0.51, bulk density: 0.45 g / cm 3 , particle size (D50): 122μm, particle size distribution (D90-D10 / D50): 0.64.

[0077] Test Method

[0078] 1. The bulk density of polyethylene is determined according to GB1636-79 (unit: g / cm 3 ).

[0079] 2. The intrinsic viscosity is measured by high temperature dilution type Ubbelohde viscometer method. The inner diameter of the capillary is 0.44mm, the constant temperature bath medium is 300 silicone oil, the dilution solvent is decahydrotetracycline, and the measuring temperature is 135℃.

[0080] 3. Mw molecular weight: tested according to GB / T 36214.4-2018 standard.

[0081] 4. Melt index is tested according to ASTM D 1238 test standard.

[0082] 5. The processing performance of the polymer is determined by measuring the initial melting point and the total melting point with a rotor rheometer. It reflects the processability of the polymer. The initial melting point usually determines the size of the polymer molecular weight. The higher the molecular weight, the higher the initial melting point. In addition to reflecting whether there are ultra-high molecular weight components in the polymer, the total melting point also reflects whether the polymer particle size is uniform, that is, whether the particle size distribution is narrow. The difference between the initial melting point and the total melting point reflects the molecular weight distribution. The narrower the molecular weight distribution, the smaller the melting point difference. The test method is as follows:

[0083] Instrument model: Rotational rheometer Anton Paar MCR101, solvent white oil, polyethylene concentration 10%. Under oscillation exploration (temperature scanning), shear strain 1%, angular frequency 10 rad / s, temperature rise from 25°C to 200°C at 3°C / min.

[0084] The preparation method of lithium battery separator is as follows:

[0085] Take 300g powder of the prepared binary polyethylene composition for lithium battery separator and stir and mix it evenly with 900g of 58# white oil; then perform banburying, the chamber of the banburying machine is about 1.5L, and add all the mixed materials. Set the temperature to 170℃, the stirring speed to 47±1rpm, and banburying for 40+20min. Observe the banburying condition after 40 minutes of banburying to see if the appearance is yellowing, transparent, and plasticized evenly. Then perform tableting.

[0086] Tableting methods include:

[0087] a. Manually scoop about 60g of the kneaded sample onto the hot plate of the tablet press, press at 180℃ and 3.3MPa for 1min;

[0088] b. Cooling to room temperature for 1 minute, pressure 3.3MPa;

[0089] c. The blade takes the sheet out of the mold and prepares for film drawing:

[0090] Film size: 1.2mm thick, inner frame 17×17cm, outer frame 23×23cm

[0091] The layers when pressing are as follows: steel plate / PI film / film mold / PI film / steel plate

[0092] The thickness of the final diaphragm is estimated based on the thickness of the membrane: 1200μm×1 / 4÷7÷7÷50% (porosity)≈12.2μm

[0093] The same film mold has slightly different film thickness due to the differences in force and heat during film pressing and film drawing; the thickness uniformity of the same film may be inconsistent.

[0094] Then the film drawing process is carried out, including:

[0095] a. Select the area with fewer defects from the 17×17cm sheet and cut it into 10×10cm, and prepare for bidirectional synchronous film drawing;

[0096] b. 5 clamps on four sides, stretching speed 15mm / s, hot air heating from bottom to top;

[0097] c. Set the temperature to 118℃ and the film drawing ratio to 1.4 times. After the sheet is clamped, preheat at a constant temperature for 5 minutes. After film drawing, heat set for 1 minute, then naturally cool down to about 70℃ and manually disassemble;

[0098] d. Set the temperature to 122℃ and the film drawing ratio to 5 times. After the sheet is clamped, preheat at a constant temperature for 5 minutes. After film drawing, heat set for 1 minute, then naturally cool down to about 70℃ and manually disassemble;

[0099] e. Clamp the membrane flat on a 45×45cm fixture for extraction.

[0100] Then the extraction is carried out, which includes:

[0101] a. Hook the fixture with an iron hook and move the membrane material to a dichloromethane tank at room temperature;

[0102] b. Immerse in three dichloromethane tanks in sequence, 7 minutes each time;

[0103] c. Take out and hang until the dichloromethane is completely evaporated;

[0104] Then heat setting is performed, including:

[0105] To prevent foreign matter or bumps, wrap the film material with clamps with PP film.

[0106] The forced air oven was set at 137°C and heat-set for 1 hour. The pieces were cut into 30×30 cm size for testing.

[0107] The test method for the performance of lithium battery separator is as follows:

[0108] The thickness of the diaphragm is tested according to GB / T6672-2001;

[0109] Air permeability is tested according to GB / T458-2008;

[0110] Porosity and surface density are tested according to GB / T24218.1-2009;

[0111] Tensile strength is tested according to GB / T1040.3-2006;

[0112] The puncture strength is tested according to GB / T23318-2009.

[0113] The test results of GPC, melt index, and intrinsic viscosity of the binary polyethylene composition for lithium battery separators, S1 standard sample, and S2 standard sample are shown in Table 1. The test results of initial melting point and total melting point of the binary polyethylene composition for lithium battery separators, S1 standard sample, and S2 standard sample are shown in Table 2. The performance test results of lithium battery separators are shown in Table 3.

[0114] Table 1

[0115]

[0116]

[0117] As can be seen from Table 1, as the content of ultra-high molecular weight polyethylene in binary polyethylene increases, the Mw of polyethylene gradually increases, the melt index gradually decreases, and the molecular weight distribution also tends to gradually increase. This shows that the binary polyethylene synthesized in the present invention is a polyethylene component with two molecular weights. After the low molecular weight polyethylene is combined with the ultra-high molecular weight polyethylene, the overall molecular weight of the binary polyethylene increases and the melt index decreases.

[0118] Table 2

[0119] Melting point(℃) Complete melting point(℃) Example 1 125.4 131.5 Example 2 125.4 133.4 Example 3 125.8 132.7 Example 4 127.6 133.4 Example 5 129.2 136.1 Example 6 126.2 132.5 Example 7 126.8 134.6 Example 8 125.4 131.8 Comparative Example 1 126.8 132.6 Comparative Example 2 130.9 137.2 Comparative Example 3 128.6 133.1 Comparative Example 4 (S1) 130.9 137.8 Comparative Example 5 (S2) 125.8 131.3

[0120] From the data in Table 2, it can be seen that although the molecular weight of the binary polyethylene composition is higher than that of S2, as the content of ultra-high molecular weight polyethylene in the binary polyethylene increases, the melting point is lower than that of S1 and S2. When the content of ultra-high molecular weight polyethylene reaches more than 40%, the melting point begins to gradually rise, but it is still lower than that of the pure reference sample. The reduction in the melting point indicates that the binary polyethylene has good processability.

[0121] Table 3

[0122]

[0123] It can be seen from the results in Table 3 that the performance of the lithium battery separator of the present invention is greatly improved compared with the single-component polyethylene (S2), showing good application prospects.

[0124] Although the present invention has been particularly illustrated and described in conjunction with the embodiments, it will be understood by those skilled in the art that various changes in form and details may be made to the present invention without departing from the spirit and scope of the present invention as defined in the claims.

Claims

1. A method for preparing a binary polyethylene composition for lithium battery separator, characterized in that: include: S1, subjecting ethylene to a first polymerization reaction to obtain a low molecular weight polyethylene having an intrinsic viscosity of 2 to 5 dl / g; the temperature of the first polymerization reaction is 60 to 80° C., the pressure is 0.4 to 0.8 mPa, and the mass ratio of ethylene to hydrogen is 6000 to 4000:1; S2, subjecting ethylene to a second polymerization reaction to obtain ultra-high molecular weight polyethylene with an intrinsic viscosity of 6 to 12 dl / g; the temperature of the second polymerization reaction is 75 to 90° C., the pressure is 0.5 to 1 mPa, and the mass ratio of ethylene to hydrogen is 4000 to 2000:1; The binary polyethylene composition for lithium battery separator comprises the low molecular weight polyethylene and the ultra high molecular weight polyethylene.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the low molecular weight polyethylene to the ultra high molecular weight polyethylene is 10-50:50-90.

3. The preparation method according to claim 1, characterized in that: The systems of the first polymerization reaction and the second polymerization reaction include a diluent, a catalyst, and a co-catalyst; Preferably, the molar ratio of aluminum in the co-catalyst to titanium in the titanium catalyst is 10-150; preferably 20-100.

4. The preparation method according to claim 3, characterized in that: The diluent includes one or a combination of two or more of hexane, isopentane and heptane; preferably, the diluent includes hexane.

5. The preparation method according to claim 3, characterized in that: The catalyst includes a Ziegler-Natta catalyst.

6. The preparation method according to claim 3, characterized in that: The co-catalyst includes an alkyl aluminum; preferably, the co-catalyst includes one or a combination of two or more of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trioctylaluminum, diethyl aluminum chloride, diisobutyl aluminum chloride, sesquiethyl aluminum chloride, and ethyl aluminum dichloride; preferably, the co-catalyst includes triethyl aluminum and / or triisobutyl aluminum.

7. A binary polyethylene composition for lithium battery separator prepared by the preparation method according to any one of claims 1 to 6.

8. The binary polyethylene composition for lithium battery separator according to claim 7, characterized in that: Meet one or a combination of two or more of the following conditions: The intrinsic viscosity is 5 to 8 dl / g; The melt index tested according to ASTMD 1238 is 0.05-0.6 g / 10 min; D50 is 110-130 microns; D90-D10 / D50 is 0.6 to 0.8; Mw is 450000~700000; Mn is 90000~130000.

9. A lithium battery separator, characterized in that: The binary polyethylene composition for lithium battery separator according to claim 7 or 8 is prepared into a film through a wet molding process, and then the film is biaxially stretched to obtain the film.

10. A lithium battery comprising the lithium battery separator according to claim 9.

Citation Information

Patent Citations

  • Ultra-high molecular weight polyethylene resin as well as preparation method and application thereof

    CN107880197A

  • High performances multimodal ultra high molecular weight polyethylene

    CN108368185A

Cited By

  • Battery diaphragm, preparation method thereof and secondary battery

    CN121307426A